Factors that affect buying decisions of secondhand garment consumers in Quiapo - Dela Cruz, Alyza Milen B.; Diez, Reynaldine; Donasco, Malia Kathlene B.; Esperanza, Ann Nicole I.; Espino, Cianne Karla; Espiritu, Denver D.; Esteves, John Patrick L.; Feria, Anne Kristine Nicole; Garcia, Celyn B. 4 0 16; 5
ABSTRACT: The act of purchasing secondhand garments, also known as thrifting, is becoming more popular these days. The acceptance of this practice has completely changed in comparison to its acceptance when it was first known. These being similar to other items, consumers also look for certain qualities these items must have before making a purchase. These qualities that consumers look for are also the factors that affect their decision whether to buy a particular item or not. The factors that affect the decision-making of a secondhand garment consumer can be influenced by different factors such as demographic profile, marketing mix, and hierarchical motivations for secondhand shopping. This study sought to answer the following questions based on the demographic profile of the respondents - their age, sex, employment status, monthly income or allowance, and frequency of buying secondhand garments. In addition, this study also provided an answer regarding the factors that affect the buying decisions of secondhand garment consumers. This study made use of a correlational approach was employed in order to explain relationship between the variables and how they affect each other. The results of this study revealed that most buyers of secondhand garments are 18 21 years old, female, and students. Aside from that, the findings also revealed the significance of marketing mix and motivations for secondhand shopping to the purchase decision of the respondents.
Business Research: (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2